Słownictwo religijne a reformacja. Głos w dyskusji nad konfesyjnym zróżnicowaniem polskiej leksyki w XVI w. - Magdalena Gozdek; Ewa Woźniak (LingVaria, 2023)
RELIGIOUS VOCABULARY AND THE REFORMATION: A CONTRIBUTION TO THE DISCUSSION ON THE CONFESSIONAL DIVERSITY OF THE SIXTEENTH-CENTURY POLISH LEXICON